Doping control analysis of emerging drugs in human plasma - identification of GW501516, S-107, JTV-519, and S-40503 - Thevis, M.; Beuck, S.; Thomas, A.; Kortner, B.; Kohler, M.; Rodchenkov, G.; Schänzer, W. (Rapid Communications in Mass Spectrometry, 2009)
An important aspect of preventive doping research is the rapid implementation of tests for emerging drugs with potential for misuse into routine doping control assays. New therapeutics of different classes such as PPAR-agonists (e.g. GW501516), ryanodine-calstabin-complex stabilizers (e.g. S-107 and JTV-519), and selective androgen receptor modulators (SARMs, e.g. S-40503) are currently used for the treatment of particular medical conditions such as metabolic syndrome, cardiac arrhythmia, debilitating diseases and osteoporosis, respectively. Due to their being at an early stage of clinical trials and the limited availability of data on the metabolism and possible renal elimination of the active drugs, the development of protocols for doping control analyses of plasma specimens could be an option for the detection of the circulating agents. The mass spectrometric fragmentation of four emerging drug candidates (GW501516, S-107, JTV-519, and S-40503) was elucidated by positive electrospray ionization and collision-induced dissociation using a high resolution/high accuracy mass spectrometer. A screening and confirmation procedure was established based on liquid chromatography/tandem mass spectrometry requiring a volume of 100 µL of plasma. Proteins were precipitated using acetonitrile, the specimens were centrifuged and the supernatant analyzed using a triple-quadrupole mass spectrometer employing multiple reaction monitoring of diagnostic ion transitions. The method was validated with regard to specificity, limits of detection (0.4-8.3 ng/mL), recoveries (72-98%), intraday and interday precisions (12-21%), and ion suppression/enhancement effects.